An Ergonomic Desk and Chair Prototype to Improve Seating Position on Senior High School Students at Kabupaten Gresik - Nilamsari, Neffrety; Soebijanto, Soebijanto; S.M., Lientje; B.R., Setokoesoemo (Jurnal NERS, 2015)
Introduction: The need of desks and chairs at school which appropriate with studentâs anthropometry are very important. Desks and chairs which not suit with studentâs anthropometry will lead to fatigue. At Kabupaten Gresik, the provision of desks and chairs which suit with studentâs anthropometry still less in number. This study was aimed to provide recomendation for an ergonomic desk and chair prototype to improve seating position on senior high school students at Kabupaten Gresik. Method: This was preexperiment research with one group pre post test design. Research subjects were students at SMAN 1 Menganti and SMAN 1 Cerme, Kabupaten Gresik, 139 students were involved. Result: The recomendation of ergonomic desks and chairs specifi cation according to studentâs anthropometry were: 1) Prototypechair N, length = 48 cm, wide = 43 cm, cushion baseâs height from floor surfaces = 47 cm, bag keeperâs height from floor surfaces =3cm, bag keeperâs wide= 43 cm, bag keeperâs length = 47 cm, cushionâs wide = 41 cm, cushionâs length = 46cm, handrestâs height = 22 cm, handrestâs length = 30 cm, backrestâs height = 38 cm, backrestâs wide = 43 cm, cushionâs foam thickness = 4 cm, backrestâs foam thickness = 4 cm; 2) Prototype desk N, length = 50 cm, wide = 66 cm, back sectionâs height = 85 cm, front sectionâs height = 75 cm, footrest from fl oor surfaces = 10 cm, drawerâs height = 10cm, front bamperâs height = 40 cm, and tableâs angle = 10o. Discussion: An ergonomic desks and chairs are very important for students at school, it will help teaching learning process run well and comfortable. The measurement of desk and chair must be reviewed after fi ve years, because of studentâs anthropometric development. So then students will feel no fatigue.Keywords: ergonomy, senior high school studentâs seating position